2020
DOI: 10.1093/ecco-jcc/jjz203.062
|View full text |Cite
|
Sign up to set email alerts
|

DOP23 Endoscopic evaluation at 1 month after ileocolic resection for Crohn’s disease predicts postoperative recurrence and is safe

Abstract: Background Endoscopic surveillance remains the gold standard for evaluating postoperative recurrence in Crohn’ disease (CD). However, the optimal timing of the first postoperative endoscopic evaluation is unclear. The commonly used strategy, first endoscopy at 3, 6, or 12 months, demonstrates high rates of endoscopic recurrence, which means this strategy may delay the detection and treatment. The aim of this study was to determine the clinical value and safety of the endoscopy at 1 month afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study showed a higher incidence of postoperative infectious complications in patients with active CD than that in patients in remission. 14 The present study suggested that disease behavior in uences the development of postoperative intestinal stula in patients with CD. Multivariate logistic regression analysis suggested that the risk was signi cantly higher in patients with stricturing CD than in patients with non-stricturing and nonperforating CD.…”
Section: Discussionmentioning
confidence: 54%
“…A study showed a higher incidence of postoperative infectious complications in patients with active CD than that in patients in remission. 14 The present study suggested that disease behavior in uences the development of postoperative intestinal stula in patients with CD. Multivariate logistic regression analysis suggested that the risk was signi cantly higher in patients with stricturing CD than in patients with non-stricturing and nonperforating CD.…”
Section: Discussionmentioning
confidence: 54%